Determinação multiclasse de fármacos e produtos de cuidado pessoal em água empregando SPE e UHPLC-MS/MS para avaliação de risco ambiental - Oliveira, Júlia Antunes de (2024)
Pharmaceuticals and personal care products (PPCPs) are substances found in medicines, cosmetics, personal care products and cleaning products. These substances can enter the aquatic environment through excretion and/or incorrect disposal, so, to assess the problem, it is necessary to know the concentrations in which they are found. Therefore, the present work aimed to develop and validate a method for the multiclass determination of PPCPs in water using solid phase extraction (SPE) and ultra-high performance liquid chromatography coupled to tandem mass spectrometry (UHPLC-MS/ MS). The samples were concentrated using the Strata-X sorbent (200 mg), with pH adjustment (6.0±0.5) and addition of EDTA (0.1%). The results of the fortification trials, evaluated at levels 0.001, 0.002, 0.01, and 0.02 μg L-1 (n=7), were between 44 and 119% with a relative standard deviation (RSD) ≤17%. The method's quantification and detection limits were 0.001 to 0.002 μg L-1 and 0.0003 to 0.0006 μg L-1, respectively. In total, 34 compounds were validated. The method was applied to the analysis of 25 water samples from different regions of Rio Grande do Sul and the results indicated that all samples were contaminated with at least 4 different compounds. From an environmental risk assessment based on the calculation of the risk quotient (RQ), it was found that losartan was the only compound with RQ>1 and, therefore, classified as high environmental risk. The proposed method was considered suitable for determining PPCPs in water and can be applied in routine laboratory analyses, toxicological tests and monitoring studies.